IMPLEMENTASI LEAN STARTUP PADA STRATEGI PENGEMBANGAN PRODUK STARTUP DIGITAL BERBASIS WEBSITE BIDANG EDUCATION TECHNOLOGY - Setiawan, Rifqi; Yuana, Pusvita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Advancements in digital technology have made digital startups in fintech, e-commerce, ride hailing, and edtech successful in solving many problems. The value of Indonesia’s digital economy is predicted to reach USD 133 billion in 2025, a highly contributive value for the state’s economy. Lesat is a digital startup in capital market investment education for Indonesians. As a newly established company, it tries to develop their products and services in order to survive in the business competition. The objective of this research is to validate ideas, create prototypes, and implement development strategy to attain product market fit. Here a qualitative descriptive method was used to process data obtained from interviews, surveys, and documentation. Using Javelin Board and SWOT Matrix, this research is able to validate ideas, creating website prototypes and informative contents in Instagram, valuating the prototypes, creating strategic options with the focus on products, services, and marketing in form of UI/UX quality enhancement, developing features and services in the website, and planning effective and efficient digital marketing.